LAJU ENDAP DARAH SEBAGAI PREDIKTOR AWAL KELUARAN PASIEN STROKE ISKEMIK AKUT - Kemal Imran* (Neurona Majalah Kedokteran Neuro Sains, 2010)
INTRODUCTION IN THE RECENT STUDY THERE IS A POSITIVE CORRELATION BETWEEN ERYTHROCYTE DEFORMABILITY THE AMOUNT OF ERYTHROCYTE AND LOW SHEAR RATE WHICH IS IMPACT TO CEREBRAL PERFUSION BY REDUCING THE CEREBRAL PERFUSION COULD BE INCREASING THE INFARCTION SIZE AND WORSENING CLINICAL MANIFESTATION